MINIMASI PEMBOROSAN PADA PRODUKSI PALLET KAYU DI PT KAYU KREASI SEJAHTERA - Eryca Siswanti; Paskaria Loyda Tarigan, Elsya (Computer Science and Industrial Engineering, 2024)
This research identified and resolved the problem of wooden pallet production at PT Kayu Kreasi Sejahtera, where the average defect rate reached 7.52%, exceeding the minimum limit of 5%. Other problems include long machine set up times, long material distances, and material buildup. The research aims to minimize Waste and offer suggestions for improving the production process. Based on the assessment, Waste due to excess transportation has the highest percentage of 27.94%, which affects other Waste. Analysis using a fishbone diagram identifies the root of the problem, which becomes the basis for recommendations for improvements such as implementing clear SOPs, scheduled machine maintenance, replacing damaged machines, rearranging material distances, adding employees, and using automatic rolling conveyors. The implementation of future state mapping shows a reduction in production lead time from 1455 minutes to 1100 minutes, increasing productivity and process cycle efficiency from 54.98% to 72.73%, recording an increase of 17.74%.